Urokinase-type plasminogen activator and plasminogen mediate activation of macrophage phagocytosis during liver repair in vivo - Kawao, Naoyuki; Nagai, Nobuo; Tamura, Yukinori; Horiuchi, Yoshitaka; Okumoto, Katsumi; Okada, Kiyotaka; Suzuki, Yasuhiro; Umemura, Kazuo; Yano, Masato; Ueshima, Shigeru; Kaji, Hiroshi; Matsuo, Osamu (Thrombosis and Haemostasis, 2012)
Urokinase-type plasminogen activator (u-PA) and plasminogen play a primary role in liver repair through the accumulation of macrophages and alteration of their phenotype. However, it is still unclear whether u-PA and plasminogen mediate the activation of macrophage phagocytosis during liver repair. Herein, we investigated the morphological changes in macrophages that accumulated at the edge of damaged tissue induced by a photochemical reaction or hepatic ischaemia-reperfu-sion in mice with u-PA (u-PA−/−) or plasminogen (Plg−/−) gene deficiency by using transmission electron and fluorescence microscopy. In wild-type mice, the macrophages aligned at the edge of the damaged tissue and extended a large number of long pseudopodia. These macrophages clearly engulfed cellular debris and showed well-developed organelles, including lysosome-like vacuoles, nuclei, and Golgi complexes. In wild-type mice, the distribution of the Golgi complex in these macrophages was biased towards the direction of the damaged tissue, indicating the extension of their pseudopodia in this direction. Conversely, in u-PA−/− and Plg−/− mice, the macrophages located at the edge of the damaged tissue had few pseudopodia and less developed organelles. The Golgi complex was randomly distributed in these macrophages in u-PA−/− mice. Furthermore, interferon γ and IL-4 were expressed at a low level at the border region of the damaged tissue in u-PA−/− mice. Our data provide novel evidence that u-PA and plasminogen are essential for the phagocytosis of cellular debris by macrophages during liver repair. Furthermore, u-PA plays a critical role in the induction of macrophage polarity by affecting the microenvironment at the edge of damaged tissue.
Keywords: u-PA; plasminogen; macrophage; phagocytosis; liver repair